1992
DOI: 10.3758/bf03330457
|View full text |Cite
|
Sign up to set email alerts
|

Effects of extinction and US reinstatement of a blocking CS-US association

Abstract: Rats were used in a conditioned taste-aversion procedure to examine the effects of extinction of a blocking CS-US association prior to the compound conditioning trials. Rats were initially given a pairing of a vinegar flavor with LiC!. Some subjects then received three extinction trials with the vinegar flavor, and other subjects were given water. Subjects were then given compound stimulus conditioning trials in which a novel sucrose flavor, the target stimulus, was followed by vinegar and then a LiCI i~ection… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

1993
1993
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 12 publications
1
5
0
Order By: Relevance
“…The procedure used to produce blocking involved only one conditioning session in each stage. Although most previous studies have used several conditioning sessions to the taste during the first stage (Batson & Best, 1979), and although the use of only one conditioning session to the compound during the second stage has not been frequent in previous studies, a procedure similar to ours has been demonstrated to be effective by Gustavson et al (1992). Thus, our results confirm the possibility of obtaining blocking with only one conditioning session in each stage.…”
Section: Blocking and Latent Inhibitionsupporting
confidence: 81%
See 1 more Smart Citation
“…The procedure used to produce blocking involved only one conditioning session in each stage. Although most previous studies have used several conditioning sessions to the taste during the first stage (Batson & Best, 1979), and although the use of only one conditioning session to the compound during the second stage has not been frequent in previous studies, a procedure similar to ours has been demonstrated to be effective by Gustavson et al (1992). Thus, our results confirm the possibility of obtaining blocking with only one conditioning session in each stage.…”
Section: Blocking and Latent Inhibitionsupporting
confidence: 81%
“…Blocking has been demonstrated in taste aversion learning (Revusky, 1977). It appears even with only one compound-aversive stimulus pairing (Batson & Best, 1979; Gustavson, Hart, Calton, & Schachtman, 1992).…”
Section: Methodsmentioning
confidence: 99%
“…Firstly, there is little human research explicitly assessing the role of awareness in such learning. Secondly, taste aversion learning in animals has been shown to obey essentially the same laws as other forms of Pavlovian conditioning, and is subject to informational manipulations such as blocking (Westbrook & Brookes, 1988), context specificity (Bonardi, Honey, & Hall, 1990) and reinstatement (Gustavson, Hart, Calton, & Schachtman, 1992). Finally, expectancy and placebo effects are well established with drug stimuli.…”
Section: Discussionmentioning
confidence: 99%
“…We reviewed the flavor-aversion experiments that reported significant flavor-flavor blocking effects, and interestingly, although we found a number of studies that reported significant blocking effects using flavors as A and X, all of these experiments employed a sequential presentation of the flavors during AX+ conditioning (e.g., Bonardi, Honey, & Hall, 1990;Gallo & Candido, 1995;Gallo, Valouskova, & Candido, 1997;Gillan & Domjan, 1977;Gustavson, Hart, Calton, & Schachtman, 1992;Moron, Ballesteros, Valouskova, & Gallo, 2001;Parker, 1986;Reilly, Bornovalova, Dengler, & Trifunovic, 2003;Willner, 1978; however, see Pierce & Heth, 2010 2 ). We posit the weakened flavor aversion following sequential compound conditioning in the A+ → AX+ design may represent a different form of the blocking effect than that observed following simultaneous compound conditioning in the AX+ phase.…”
Section: Discussionmentioning
confidence: 97%